2013
DOI: 10.1590/s1414-753x2013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Diretiva Quadro D'Água: uma revisão crítica e a possibilidade de aplicação ao Brasil

Abstract: IntroduçãoApesar da lei n° 9433/97, que estabelece a Política Nacional de Recursos Hídricos (PNRHI) e o Sistema Nacional de Gerenciamento dos Recursos Hídricos (SINGREH) (BRASIL, 1997), ter representado um grande avanço na gestão de RH, ainda é precária a situação em que se encontram muitos corpos hídricos no Brasil. A PNRHI e o SINGREH estabelecem uma série de medidas promitentes, que provavelmente trarão resultados eficazes na preservação das águas, mas muito ainda pode e deve ser feito no sentido de aprimor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
2
3
0
6
Order By: Relevance
“…The areas of lowest copper concentration were located southwards, distant from the dam. This copper spatial pattern was in general agreement with the results obtained by Pompêo et al (2013). However, Pompêo et al found a minimum copper concentration of 9.2 mg (copper) /kg (dry sediment) in this reservoir, while the minimum copper concentration observed in the present work was at least 10-fold higher.…”
Section: Sediment Copper Evaluationsupporting
confidence: 93%
See 2 more Smart Citations
“…The areas of lowest copper concentration were located southwards, distant from the dam. This copper spatial pattern was in general agreement with the results obtained by Pompêo et al (2013). However, Pompêo et al found a minimum copper concentration of 9.2 mg (copper) /kg (dry sediment) in this reservoir, while the minimum copper concentration observed in the present work was at least 10-fold higher.…”
Section: Sediment Copper Evaluationsupporting
confidence: 93%
“…Fig. 7 illustrates the proportions of the ELU quality classes, with 89% of the ELU area being above the ISQG, 52% above the PEL, and 44% 10-fold greater than the PEL, in agreement with previous reports (CETESB, 2013;Pompêo et al, 2013). The northern region of the reservoir, closer to the SABESP water collection system, showed the worst sediment quality (Fig.…”
Section: Qualitative Copper Statussupporting
confidence: 88%
See 1 more Smart Citation
“…The quality standards are laid down in Federal and State laws, and aim to ensure the quality of water used for human purposes (CONAMA 357/ 2005). CETESB has monitored chemical and physical water quality parameters in rivers and reservoirs for more than 10 years and could be considered a referential environmental agency in Brazil and South America (Cardoso- Silva et al, 2013).…”
Section: Study Sitementioning
confidence: 99%
“…Com isso, lições podem ser tiradas de modelos de gestão aplicados em diversos países, como o modelo de gerenciamento de RH europeu, a Diretiva Quadro da Água (DQA). Essa diretiva está contribuindo com a recuperação dos corpos hídricos europeus, assim poderia se tornar um exemplo para o processo de gestão dos recursos hídricos brasileira (Cardoso- Silva et al, 2013).…”
Section: Introductionunclassified